Persepsi Penonton Terhadap Pentas Pertunjukan Wayang Yayasan Kertagama Jakarta - Sudarsono Sudarsono; Harijadi Tri Putranto; ER Elis Noviati Dewi Mariani (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
In 2010, the Kertagama Foundation in collaboration with ISI Surakarta organized a puppet show. Research on puppet show audiences has been extremely rare. The approach used in this study belongs to Talcott Parson's thinking about the functional theory of action. The results of the study tell that the audience comes from different ages and different social status. The school age sees wayang because of their parents. the adolescent audience sees wayang to add their knowledge related to the art education they are learning. The adult audience sees wayang performances as a hobby to satisfy themselves. By watching a puppet show, adults feel that they have learned about life lessons so that they can become spiritually satisfied. Among the audiences, there are groups of them who just watch wayang performances, for example accompanying their girlfriends, their employers, or their parents.